Triple-Loaded Nanoemulsions Incorporating Coffee Extract for the Photoprotection of Curcumin and Capsaicin: Experimental and Computational Evaluation - Boonrueang, Nuttapol; Chaichit, Siripat; Yooin, Wipawadee; Okonogi, Siriporn; Kiattisin, Kanokwan; Ampasavate, Chadarat (Pharmaceutics, 2025)
Background/Objectives: This study aims to present a strategic approach to enhancing the photostability and antioxidative resilience of curcumin and capsaicin by integrating selected natural stabilizers within a nanoemulsion-based delivery system. Methods: Coffee extract (Coffea arabica Linn.), along with its active components and vitamin E-containing natural oils, was assessed in terms of improving the photostabilizing and antioxidative retention abilities of curcumin and capsaicin. An optimized ratio of the active mixture was then loaded into a nanoformulation. Results: The analysis of active contents with validated high-performance liquid chromatography (HPLC), ferric reducing antioxidant power (FRAP), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays confirmed the stabilization enhancement after irradiation with UV and white light for 72,000–84,000 lux hours. The optimized combination of coffee extract with turmeric and chili mixtures loaded into the optimized nanoemulsion enhanced the half-lives (T1/2) of curcumin and capsaicin by 416% and 390%, respectively. The interactions of curcumin and capsaicin with caffeine and chlorogenic acid were elucidated using computational calculations. Interaction energies (Eint), HOMO-LUMO energy gap (HLG) analysis, and global reactivity descriptors revealed hydrogen bonding interactions be-tween capsaicin and chlorogenic acid, as well as between curcumin and caffeine. Conclusions: By leveraging the synergistic antioxidative properties of coffee extract and vitamin E within a nanoemulsion matrix, this study overcomes the intrinsic stability limitations of curcumin and capsaicin, offering a robust platform for future pharmaceutical and nutraceutical applications.